The European Union and the Baltic counter-offensive on the rule of law. The 2020 Rule of Law Report in Latvia and Lithuania (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
Notwithstanding the global expansion of phenomena of regression and erosion affecting liberal democracies, after having been subjected to the occupation of totalitarian regimes in the 20th century, the newly independent Republics of Latvia and Lithuania are now pursuing policies aimed at improving the rule of law. The present contribution seeks to analyse from a comparative perspective the advancement of recent reforms undertaken by the two Baltic Republics.
Keywords: Latvia; Lithuania; Rule of Law; European Union; Reforms